Chemical composition of leaf and seed essential oil of Coriandrum sativum L. from Bangladesh - Md. Nazrul Islam Bhuiyan, Jaripa Begum and Mahbuba Sultana (Bangladesh Pharmacological Society, 2009)
The essential oils from leaves and fruits of Coriandrum sativum L. were analyzed by gas chromatography mass spectroscopy (GC-MS). The leaf oil contained 44 compounds mostly of aromatic acids containing 2-decenoic acid (30.8%), E-11-tetradecenoic acid (13.4%), capric acid (12.7%), undecyl alcohol (6.4%), tridecanoic acid (5.5%) and undecanoic acid (7.1%) as major constituents. The seed oil contains 53 compounds where the major compounds are linalool (37.7%), geranyl acetate (17.6%) and γ-terpinene (14.4%). The compositions of both oils varied qualitatively and quantitatively.